Cocurricular Assessment: Aligning Service-Learning With General Education Goals - Ruth Boyd, G. Allen Boyd, Taler Alexander (Educational Process: International Journal, 2022)
Background/purpose – Cocurricular offerings should appropriately align with academic learning goals to ensure undergraduate students’ development of professional dispositions that lead to civic and career success. This study provides a framework for implementing high impact practices into cocurricular instruction, as well as steps on how to align this instruction to the general educational goals of institutions.